WHEN SUSTAINABILITY MEETS FINANCE: HOW ESG-LINKED INSTRUMENTS AND CAPITAL STRUCTURE OPTIMIZATION SHAPE CORPORATE FINANCIAL PERFORMANCE - Vinh, Vo Minh; Ngoc, Dang Le Khanh; Tran, Hoang Ngoc Bao (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigates the relationship between ESG-associated financing and capital structure optimization, as well as their subsequent impact on corporate financial performance (CFP) within the financial services sector. It highlights the moderating role of market uncertainty and aims to fill existing gaps in the literature by empirically evaluating the effectiveness of sustainability-driven financial strategies in dynamic market environments. Employing a quantitative research design, this study surveyed 385 professionals from banks, insurance companies, and fintech firms located in Southeast Asia, utilizing stratified random sampling methods for data collection. The analysis employed descriptive statistics, Cronbach’s Alpha for reliability assessment, Exploratory Factor Analysis (EFA) for construct validation, and multiple linear regression analysis via SPSS to test the research hypotheses. The findings indicate that ESG-associated investment has the most significant influence on CFP (β = 0.534), closely followed by capital structure optimization (β = 0.427). Additionally, market uncertainty serves as a moderator for both relationships (β = 0.367 and β = 0.421, respectively), with its effects becoming more pronounced during volatile conditions. These results highlight that ESG strategies and optimized capital structures are not only performance-enhancing but also crucial resilience mechanisms under uncertainty. The study contributes to signaling, trade-off, and institutional theories by contextualizing ESG-financial decisions in emerging markets. Practically, financial institutions and policymakers should integrate ESG-linked financing instruments and flexible capital planning to improve performance and stability under volatile market conditions.